Resso Media in Teaching English Vocabulary Mastery: A Lyrics of Song Approach - Umar; Narmayani (Universitas Sulawesi Barat, 2023)
This study aims to determine the effect of using Media Resso on students' vocabulary mastery in the eighth grade (8) SMPN 2 Majene. This research is quantitative using a quasi-experimental design, and the subject of this research is 40 students. This study uses Cluster Random Sampling to determine the sample. Data was collected using pre-test and post-test instruments consisting of 20 questions in the form of Fill In The Blank and Matching words. The data analysis technique used is the Paired sample t-test with the SPSS version 20 application for windows. The results of the research analysis indicate that the average post-test score is 74.25, which is higher than the pre-test average value, which is 49.75. This means that Ha is acceptable. Therefore, Resso Media can affect students' vocabulary mastery after being given treatment.